Evaluating equality in psoriasis healthcare: a cohort study of the impact of age on prescription of biologics3. (4th February 2016) - Geale, K.; Henriksson, M.; Schmitt‐Egenolf, M.
Summary: Background: Inequality in healthcare has been identified in many contexts. To the best of our knowledge, this is the first study investigating age inequality in the form of prescription patterns of biologics in psoriasis care. Objectives: To determine whether patients with psoriasis have equal opportunities to receive biological medications as they age. If patients did not receive equal treatment, a subsequent objective was to determine the magnitude of the disparity. Methods: A cohort of biologic‐naive patients with psoriasis was analysed using Cox proportional hazards models to measure the impact of each additional year of life on the likelihood of initiating biological treatment, after controlling for sex, body mass index, comorbidities, disease activity and educational level. A supporting analysis used a nonparametric graphical method to study the proportion of patients initiating biological treatment as age increased, after controlling for the same covariates. Results: The Cox proportional hazards model resulted in hazard ratios of a 1‐year increase in age of 0·96–0·97 depending on calendar‐year stratification, which implies that an increase in age of 30 years corresponds to a reduced likelihood of initiating biological treatment by 61·3–67·6%. The estimated proportion of patients initiating biological medication always decreased as age increased, at a statistically significant level. Conclusions: Patients with psoriasis have fewer opportunities to access biological medications as they age. This result was shown to be applicable at all stages in a patient's life course and was not only restricted to the elderly, although it implies greater disparities as the age difference between patients increases. These results show that inequality in access to biological treatments due to age is prevalent in clinical practice today. Further research is needed to investigate the extent to which this result is influenced by patient preferences. Abstract : What's already known about this topic? Inequalities in healthcare have been identified in many contexts, prompting political policy to focus on their reduction. Older patients may not have the same opportunities to access healthcare as younger patients with similar clinical profiles. This trend has been shown in the majority of research in rheumatoid arthritis, a field that uses many of the same biological treatments as psoriasis. What does this study add? The first examination of the relationship between age and access to biological medication in psoriasis. Patients are less likely to receive prescriptions for biological treatments as they age. An increase of 30 years in age leads to a 61·3–67·6% decrease in the likelihood of receiving access to biological treatments, after controlling for covariates. Evidence of age inequality in access to biological treatments for patients with psoriasis. Plain language summary available online